PERANAN SISTEM INFORMASI MANAJEMEN AKUNTANSI BARANG MILIK NEGARA DALAM MENUNJANG AKUNTABILITAS PENGELOLAAN BARANG MILIK NEGARA (Studi Kasus di Pusat Penelitian Geoteknologi LIPI Bandung) - Muhamad Nur Afandi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2012)
Accounting Management Information System State Property is an application program to facilitate the attainment of information on the management of state property and report to any governmental agency. The purpose of this study isto investigate the application of Accounting Management Information System application of State Assets, implementation and management of State Owned Assets aware management accountability Negaradi Research Centerfor Geotechnology. The method used in this research is descriptive research with a qualitative approach, which aims to uplift the facts, circumstances and phenomena that occur when the research took place, while the data collection technique is implemented by observing the social situation, interviews with respondents, and study documentation. Based on the results of the study showed that the application of Accounting Management Information System State Property is very important in the management of BMN Geotechnology Research Center, although in terms of management of the State Property Geotechnology Research Center assessed qualitatively not run well, especially in the case of an inventory of state property. But the application of Accounting Management Information System State Property is very important in the management of goods that can be accounted for in accordance with the implementation peratuan legislation in force.